Niech ktoś pomoże już 2 razy mi ktoś usuną pytanie
(−5) ∙ (−7) = (−3) ∙ 7 = (−2) ∙ (−2) =
(−21) ∶ 7 = (−4) ∶ (−2) = 45 ∶ (−9) =
4 ∙ (−6) = (−1) ∙ (−5) = (−4) ∙ 8 =
15 ∶ (−3) = (−6) ∶ 2 = (−56) ∶ (−8) =



Odpowiedź :

Odpowiedź:

(−5) ∙ (−7) =35

(−3) ∙ 7 = -21

(−2) ∙ (−2) = 4

(−21) ∶ 7 =-3

(−4) ∶ (−2) =2

45 ∶ (−9) = -5

4 ∙ (−6) =-24

(−1) ∙ (−5) =5

(−4) ∙ 8 = -32

15 ∶ (−3) = -5

(−6) ∶ 2 = -3

(−56) ∶ (−8) =7

Szczegółowe wyjaśnienie:

Odpowiedź:

(-5)*(-7)= 35

(-3)*7= - 21

(-2)*(-2)=4

(-21):7= - 3

(-4) : (-2)= 2

45 : (-9)= (-5)

4*(-6)= - 24

(-1) *(-5)= 5

 (-4)*8= - 32

 15 : (-3)= - 5

     

 (-6) : 2= -3

(-56) : (-8)= 7

Szczegółowe wyjaśnienie: